2018
DOI: 10.1589/jpts.30.365
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mechanical-bed massage on exercise-induced back fatigue in athletes

Abstract: [Purpose] The study aimed to preliminarily investigate the effects of mechanical-bed massage on exercise-induced back fatigue in athletes. [Subjects and Methods] Twelve male college athletes, randomly allocated to experimental or control groups, were instructed to perform reverse sit-up for 8 sessions until they became fatigued. The experimental group received a 20-min mechanical-bed massage session, while the control group rested on a bed for the same period of time. Visual Analogue Scale (VAS) on perceived b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…With rapid recent technological developments, manual techniques can be implemented using mechanical devices without the need for manual handling; hence, mechanical massage can be performed using a skilled manual technique at any time in a private, convenient, and controlled setting [ 19 , 20 ]. Previous studies demonstrated the effects of mechanical massage on stress [ 21 ]; mental fatigue and cognitive function [ 22 ]; heart rate, blood pressure, and temperature [ 23 ]; muscle relaxation [ 19 ]; and muscle fatigue and sympathetic and parasympathetic balance [ 24 ]. Mechanical back massage releases the erector spinae while simultaneously gliding the thoracic spine vertically with a mobilization effect that extends by segment.…”
Section: Introductionmentioning
confidence: 99%
“…With rapid recent technological developments, manual techniques can be implemented using mechanical devices without the need for manual handling; hence, mechanical massage can be performed using a skilled manual technique at any time in a private, convenient, and controlled setting [ 19 , 20 ]. Previous studies demonstrated the effects of mechanical massage on stress [ 21 ]; mental fatigue and cognitive function [ 22 ]; heart rate, blood pressure, and temperature [ 23 ]; muscle relaxation [ 19 ]; and muscle fatigue and sympathetic and parasympathetic balance [ 24 ]. Mechanical back massage releases the erector spinae while simultaneously gliding the thoracic spine vertically with a mobilization effect that extends by segment.…”
Section: Introductionmentioning
confidence: 99%
“…However, Do-Kim et al [21] had incorporated heating to the mechanical bed massage intervention to examine the combined effect. Zhong et al [52] reported no statistically significant difference in back muscle extension (BME) between massage and control group. The study noted the slower rate of decline in BME in massage group, which they associated with increased blood flow and elimination of metabolites, but the evidence was not conclusive.…”
mentioning
confidence: 97%
“…Two studies investigated on the effect of mechanical bed massage on lower back muscle fatigue, strength, and recovery. In one study by Zhong et al [52], the researchers induced muscle fatigue through reverse sit ups in prone position followed by mechanical bed massage and evaluated back muscle endurance immediately, and 24 h after the intervention. The sample for this study comprised entirely of athletes.…”
mentioning
confidence: 99%
“…Compressent garment has been proposed to prevent performance degradation and improve recovery by speeding up nutrient delivery, improving post-workout edema, muscle soreness (DOMS), and muscle damage. The use of compressent garment can minimize the symptoms of muscle damage due to exercise (EIMD) which usually occurs as a result of unusual or eccentric exercise [4].According to Molly Winke et al [37]in their study, the muscle swelling assessed through changes in upper arm circumference was significantly lower in treatment compressed garment (1.7 vs 2.0 cm in compressed sleeves, p = 0.012).Interference ROM during Compressent Garments (PCD) treatment was lower and peak pain was 39% lower (27.5 mm in PCD compared to 45.2 mm in the compress arm (CS), p <0.05. using compressent garments further reduces the peak disturbance and recovery time from DOMS (Delayed Omzet Muscle Sorrenes).…”
Section: Resultsmentioning
confidence: 99%